2000
DOI: 10.1083/jcb.150.6.1499
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Lethality of Molecular Chaperone Hsp47 Knockout Mice Is Associated with Defects in Collagen Biosynthesis

Abstract: Triple helix formation of procollagen after the assembly of three α-chains at the C-propeptide is a prerequisite for refined structures such as fibers and meshworks. Hsp47 is an ER-resident stress inducible glycoprotein that specifically and transiently binds to newly synthesized procollagens. However, the real function of Hsp47 in collagen biosynthesis has not been elucidated in vitro or in vivo. Here, we describe the establishment of Hsp47 knockout mice that are severely deficient in the mature, propeptide-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
286
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 321 publications
(307 citation statements)
references
References 33 publications
20
286
0
1
Order By: Relevance
“…The milder pheno type in humans probably results from residual serpin H1 function. Serpinh1-null mice are embryonically lethal 69 , owing to aggregation of improperly folded collagen in the rER, delayed collagen secretion and eventually defective collagen fibrillogenesis 70 .…”
Section: Box 1 | Classification Of Osteogenesis Imperfectamentioning
confidence: 99%
“…The milder pheno type in humans probably results from residual serpin H1 function. Serpinh1-null mice are embryonically lethal 69 , owing to aggregation of improperly folded collagen in the rER, delayed collagen secretion and eventually defective collagen fibrillogenesis 70 .…”
Section: Box 1 | Classification Of Osteogenesis Imperfectamentioning
confidence: 99%
“…These enzymatic modifications are highly coordinated and include removal of the signal peptide in the endoplasmic reticulum (ER), hydroxylation of many proline and lysine residues, glycosylation of specific hydroxylysine residues, addition of mannose-rich oligosaccharide, and finally the formation of important intrachain disulfide bonds between the 12 conservative cysteine residues in the NC1 domain. In addition, biosynthesis of collagens is highly dependent on at least one specific molecular chaperon, Hsp47, without which proper folding will not take place (Matsuoka et al, 2004;Nagai et al, 2000).…”
Section: Biosynthesis and Modificationsmentioning
confidence: 99%
“…Heat shock protein 47 (HSP47), a collagen-specific molecular chaperone, is essential for the biosynthesis and secretion of collagen molecules (Nagata 1996;Nagata et al 1986Nagata et al , 1988Ishida et al 2006;Nagai et al 2000;Sauk et al 1994). Previous studies of various experimental diseases affecting the lungs have shown that there is a close association between increased expression of HSP47 and excessive accumulation of collagen (Ishii et al 2003;Kakugawa et al 2004Kakugawa et al , 2010.…”
Section: Introductionmentioning
confidence: 99%